Proportional Resonant Controlled Dual Active Bridge DC to AC Converter System with Enhanced Response - R. Sowmya; S. Rama Reddy (Institute of Advanced Engineering and Science, 2018)
This paper deals with comparison of responses of PI and Proportional Resonant controlled DC to AC Converter systems. The objective of this work is to regulate the output of Dual Active Bridge DC to DC converter (DABDAC). The input DC is converted into high frequency AC using Half bridge inverter. It is stepped up by using step up transformer and then it is rectified. The DC is converted into Low frequency AC using a Half bridge inverter. The open loop DABDAC system, closed loop PI based DABDAC system an Proportional Resonant Controller (PRC)based DABDAC system are designed, modeled and simulated using MATLAB Simulink. The results of PR controlled system are compared with those of PI controlled system. The results indicate that the proposed PRC-DABDAC has better time domain response than PI controlled DABDAC system. The proposed DABDAC system has advantages like high gain and steady state error in output voltage.